Placenta previa: outcomes in scarred and unscarred uterus - Katke, Rajshree Dayanand (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: Placenta previa complicates 0.3% - 0.5% of all pregnancies and is a major cause of third-trimester hemorrhage. Almost 30 % maternal deaths in the Asian population are due to major obstetrical haemorrhage in placenta previa, especially due to rise in the incidence of cesearean sections. Significant maternal morbidity in the form of increased incidence of fetalmalpresentation, cesearean delivery, increased blood loss and peripartum hysterectomy have been noted in cases of placenta previa and can lead to prolonged hospitalization in these women. Premature deliveries can occur which lead to higher admission to neonatal intensive care unit and stillbirths. Methods: This retrospective study was conducted in the Department of Obstetrics and Gynecology at Cama and Albless Hospital (Sir J.J Group of Hospitals), Mumbai. Cases of placenta previa from January 2013 to December 2015 were studied. Results: Significantly high number of patients delivered before 37 weeks of gestation in Group A (66.7%) than that in group B (20%). (p=0.003, Hsig). There was only case of placenta accreting in Group A (6.7%) and only this patient required an obstetric hysterectomy. Both Groups showed a favourable fetal outcome (Group A 100%, Group B 96%). Conclusions: In conclusion, primary prevention in the form of reduction in the rate of primi cesearean section must be done in order to prevent likelihood of placenta previa in scarred uteri. Early diagnosis by Ultrasound and planned delivery should be the goal.